Empowerment of Tempeh Producers in Managing Soybean Wastewater into Liquid Organic Fertilizer through Participatory Action - Wangi, Nisaul Barokati Seliro; Hasbullah, Afif; Jian, Li (Bisma : Bimbingan Swadaya Masyarakat, 2024)
This community engagement program aimed to address the environmental problem of untreated liquid waste generated by household-scale tempeh production in Plaosan Village. Using a participatory action research approach, the program facilitated collaborative learning, hands-on fermentation training, and reflective planning with 35 tempeh-producing households. The intervention focused on transforming nutrient-rich soybean wastewater into a usable liquid organic fertilizer (LOF) using EM4 technology and local materials. The results indicated significant improvements in environmental knowledge, fermentation skills, and behavioral change: post-test knowledge scores increased by 44.5%, and 77% of participants reduced direct waste discharge. Moreover, three women emerged as peer educators, leading micro-replication efforts. This initiative demonstrated that dialogical, experiential learning can successfully promote sustainable waste management practices, empower local actors, and catalyze grassroots environmental stewardship.